Heideggerowski zwrot: jedność bycia i nieantropocentryczna filozofia człowieka - Hoły-Łuczaj, Magdalena (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2013)
The article aims to show that one of the most important manifestations of Turn in the philosophy of Martin Heidegger is a change of the ontological status of beings other than human. Transformation of Dasein into Da-sein (which takes place in Heidegger's works written between year 1930 and 1936) is accompanied by the recognition of being of other beings, "things" (concrete individuals, animate and non-animated). While in Being and Time, other entities are considered "lower" than the man, and unlike him, not "are", but only "are-handy" or "mere-live", What is a Thing? (and even already Introduction to the Metaphysics) indicates the unity of being. This does not mean the rejection of the specificity of the human being as Da-sein. Only thanks to human being – not just his own, but also of other beings – is no longer hidden. The specific nature of man according to Heidegger, however, does not entitle him to dominate other beings and treated as a subordinate. Thus I consider late philosophy of Heidegger as non-anthropocentric.